Increasing the dietary supply of carotenoids through forage supplementation: Effect on nitrogen and mineral retention in captive Golden pheasants (Chrysolophus pictus). Issue 6 (13th September 2016) - Kullu, Singray Saleb; Das, Asit; Saini, Mohini; Garg, Anil Kumar; Yogi, Ravindra Kumar; Soren, Shyamal Kumar; Sharma, Anil Kumar
Abstract : This experiment was conducted to evaluate the effects of feeding different levels of green forages on feed consumption, nutrient and mineral utilization in Golden pheasants (GP). Twenty‐seven female GP (BW 617–635 g) were randomly distributed into three groups of nine birds each in an experiment based on completely randomized design (CRD). Birds in group T 1 were fed a conventional zoo diet containing 1.4% green forages; however, the diets of the birds in groups T 2 and T 3 contained 2.7% and 5.0% of green forages, respectively. Intake of total carotenoids increased with increased level of green forages in the diet. Apparent retention of N, Ca, and Zn was higher in GP laying hens fed diet containing 5.0% green forages as compared to those fed conventional diet containing 1.4% green forages. Results of the present study indicate that inclusion of 5% green forage in the diet of GP would improve the utilization of N, Ca, and Zn without any adverse effect on intake and utilization of other nutrients. Data related to nutrient intake, basal endogenous losses (BEL) and coefficient of retention (COR) of N, Ca, P, Mg, Fe, Cu, Mn, and Zn are novel and may be of use for future research. Zoo Biol. 35:522–532, 2016. © 2016 Wiley Periodicals, Inc.